DOP49 Quantitative proteomics analysis of macrophages from Crohn’s disease patients and infected with adherent-invasive Escherichia coli - Douadi, C; Vazeille, E; Chambon, C; Hébraud, M; Dodel, M; Pereira, B; Coban, D; Buisson, A; Barnich, N (Journal of Crohn's and colitis, 2020)
Abstract Background Crohn’s disease (CD) is a disabling inflammatory bowel disease. Currently, the available treatments only alleviate the symptoms. The anti-TNFα represent the most efficient therapeutic class, but its mechanisms are poorly known. Experimental data have highlighted the role of intestinal macrophages in the pathogenesis of CD. These macrophages present a defect in the control of CD-associated adherent-invasive E. coli (AIEC) replication, which is linked to altered autophagy. The main aim of this study was to compare the proteomic profile of macrophages from CD patients with and without anti-TNFα treatment, to those from ulcerative colitis (UC) patients or healthy subjects, both at the basal state and after AIEC infection. Methods Peripheral blood monocyte-derived macrophages (MDM) were obtained from 44 CD patients including 22 with and 22 without anti-TNFα treatment, 22 UC patients and 22 healthy subjects. MDM was infected or not with AIEC LF82 reference strain. The numbers of intracellular bacteria were determined at 1h and 6h post-infection, using gentamicin protection assay. The ‘bottom-up’ proteomic analysis of macrophages after 6h of AIEC LF82 infection or not, was assessed by a mass spectrometer, using the label-free quantification. Results AIEC survival was reduced within MDM from CD patients with anti-TNFα treatment compared with those from CD without TNFα treatment (p = 0.0235). The proteomic analysis identified 1359 proteins, of which, 71 were differentially expressed between MDM at the basal state and infected by AIEC LF82 whatever the origin, 30 proteins were specific in CD patients with anti-TNFα treatment and 16 in CD patients without anti-TNFα treatment (fold change >1.3). The bioinformatics analysis shows an impact of several pathways involved in cellular activation, immune process and lysosomal activity. Interestingly, CD macrophages expression levels of β3 integrin (ITGB3), glutathione peroxidase-1 (GPx-1) and peroxiredoxin 3 (PRDX3) are significantly correlated with AIEC survival at 6h post-infection and faecal calprotectin. The stratification of MDM from CD patients according to the level of faecal calprotectin highlighted that levels of calprotectin and α-L-Fucosidase 1 (FUCA-1) increased in a similar way, both at the basal state and after AIEC LF82 infection. Conclusion Our study highlighted that the anti-TNFα treatment limits bacteria replication and acts on macrophages function. For the first time, global proteomic analysis suggests that CD macrophages-AIEC interaction could be orchestrated by ITGB3, GPx-1, PRDX3 and FUCA-1. These proteins could represent potential therapeutic targets in CD patients that need to be further investigated.